Changes in mechanical properties of dental alloys induced by saliva and oral probiotic supplements. Issue 1 (27th January 2020) - Musa Trolic, I.; Turco, G.; Contardo, L.; Perissinotto, F.; Katic, V.; Spalj, S.
Abstract: The effects of the saliva and oral probiotic supplements on roughness, friction and microhardness of the stainless steel (SS) and nickel‐titanium (NiTi) alloys used in dentistry was studied. The specimens of stainless steel, uncoated, rhodium‐coated and nitrided NiTi were exposed to artificial saliva with pH 4.8 and artificial saliva with addition of probiotic supplements containing bacteria Lactobacillus reuteri Prodentis through 28 days. First 5 days specimens were subjected to thermocycling to simulate intraoral conditions, 2500 cycles from 5 °C to 50 °C and the following days to the temperature of the 37±2 °C. Analyses demonstrated that oral probiotic supplements do not influence microhardness, roughness or friction of stainless steel above the influence of saliva. Probiotics increase roughness in NiTi, but without significant influence on friction, while microhardness in NiTi is not influenced. Surface nitriding reduces the influence of probiotics on roughness while rhodium coating increases it. Abstract : A possibility of microbial induced corrosion of dental alloys by probiotic supplements containing Lactobacilus reuteri was examined. Analyses of roughness, friction and hardness of the stainless steel and nickel‐titanium demonstrate that oral probiotic supplements in saliva do not induce major changes in mechanical properties of alloys in comparison with the effect of saliva alone. Translation abstract: Die Einflüsse des Speichels und oraler Probiotika auf die Rauigkeit, Reibung und Mikrohärte von Edelstahl und Nickel‐Titan‐Legierungen, die in der Zahnmedizin angewendet werden, wurden untersucht. Es wurden unbeschichtete und Rhodium beschichtete Edelstahlproben sowie nitrierte Nickel‐Titan‐Legierungen bei den Versuchen berücksichtigt. Die Proben wurden künstlichem Speichel mit pH 4, 8 ausgesetzt und dem Speichel mit Zusatz von Probiotikum, der das Bakterium Lactobacillus reuteri Prodentis enthält, für 28 Tage ausgesetzt. Für die ersten 5 Tage wurden die Proben mit 2500 Zyklen von 5 °C bis 50 °C thermocycliert, um die intraoralen Umstände zu simulieren und die nächsten Tage bei der Temperatur von 37±2 °C. Die Analysen bzw. Ergebnisse zeigen, dass die oralen Probiotika die Rauigkeit, Reibung und Mikrohärte des Edelstahls nicht mehr beeinflussen als Speichel. Die Probiotika vergrößern die Rauigkeit der Nickel‐Titan‐Legierungen, haben aber keinen bedeutsamen Einfluss auf die Reibung und die Mikrohärte der Nickel‐Titan‐Legierungen. Das Nitrieren der Oberfläche reduziert den Einfluss der Probiotika auf die Rauigkeit während sie die Rauigkeit der Rhodium‐Beschichtung vergrößert.